The Trinity Technique: A novel 3-step approach for debriefing interprofessional major incident simulation. - Newton, Jon (International Journal of Practice-based Learning in Health and Social Care, 2025)
Debriefing is conducted following serious or unexpected incidents to support well-being, uphold professional standards and help organisations pledge a duty-of-care. Debriefing skills can be honed within Simulation-Based-Learning (SBL) activities and a range of studies have shown this approach effective at transforming experiences into meaningful reflection. Immediately congregating learners after the conclusion of a simulation to identify areas of strength and growth and outlining potential areas to enhance future practice has also been shown to help cement key learning objectives. Despite this, the wider literature lacks a validated tool for interprofessional major incident simulation, highlighting an important research-knowledge gap. As part of a quality improvement initiative to advance teaching and learning practices within this domain, a novel 3-step, interprofessional major incident simulation debriefing strategy titled the Trinity Technique was fashioned and pilot-tested amongst a sample of 436 students studying Paramedic Science, Adult Nursing, Physician Associate Studies and Forensic Science. The Trinity Technique received positive feedback, valuable insight into learner experience was gained and the novel approach had a unique ability to debrief institutions as well as learners. Further research is now required to formally validate this pioneering approach.